Courtship and love among the enslaved in North Carolina - Fraser, Rebecca J., 1978- (Margaret Walker Alexander series in African American studies., 2007)
Through an examination of various couples who were forced to live in slavery, Rebecca J. Fraser argues that slaves found ways to conduct successful courting relationships. In its focus on the processes of courtship among the enslaved, this study offers further insight into the meanings that structured intimate lives. Establishing their courtships, often across plantations, the enslaved men and women of antebellum North Carolina worked within and around the slave system to create and maintain meaningful personal relationships that were both of and apart from the world of the plantation. They cl.